Impact of the spatial and temporal resolution of precipitation inputs for hydrological modeling in West Africa and implication in the use of satellite products : Case study on the basin of Ouémé in Benin - (:unkn) unknown (My University, 2016)
Intertropical climates are characterized by a strong space-time variability of precipitation that can produce persistent dry spells and extreme rainfall events within the same region. These extreme climatic conditions directly impact water resources and flood occurrences, threatening populations that are highly vulnerable to natural hazards. This is especially the case in West Africa, where an increasing number of flood events has been reported over the last twenty years while the dry conditions that have started in the 1970's still prevail nowadays. While a significant climate warming is already observed in this region, there is more to come, with possible changes of the patterns of rainfall variability. It is thus of primary importance to better apprehend how sensitive is the hydrological response of West African catchments to small scale rainfall variability. Numerical models explicitly simulating the hydrological processes have already been tested and calibrated to represent the rainfall-runoff relationship of these catchments. They require high resolution (typically a few kilometers in space and one hour or less in time) rainfields as inputs, so as to account properly for the small scale variability of precipitation. However, this requirement is difficult to meet in a region where operational networks have a density which often does not exceed one gauge per 10000 km² and provide daily measurements only. Satellite remote sensing is consequently seen as a remedy to the shortcomings of ground monitoring, especially as it provides a continuous monitoring in space and time, but satellite rainfall products are still far from reaching the high space-time resolution mentioned above. In such a context, the sensitivity of hydrological models to the resolution of their forcing rainfields is an important topic, rarely tackled as such in the literature dealing with hydrological modeling based on satellite data.This PHD thesis thus focus on two related questio
Keywords: African Research